2014
DOI: 10.1152/jn.00652.2012
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of layer 4 during development increases GABAAreceptor neurotransmission in the neocortex

Abstract: Abbah J, Braga MF, Juliano SL. Targeted disruption of layer 4 during development increases GABA A receptor neurotransmission in the neocortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…We also observed that interneurons migrating into the neocortex from the ganglionic eminence specifically altered their speed and pattern of movement after MAM treatment [6]. Furthermore, MAM-treated brains have increased levels of GABA Aα receptors and KCC2 protein at neonatal ages [6], and GABA Aα receptors in older animals [17].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…We also observed that interneurons migrating into the neocortex from the ganglionic eminence specifically altered their speed and pattern of movement after MAM treatment [6]. Furthermore, MAM-treated brains have increased levels of GABA Aα receptors and KCC2 protein at neonatal ages [6], and GABA Aα receptors in older animals [17].…”
Section: Introductionmentioning
confidence: 61%
“…After treatment with MAM in pregnant ferrets during corticogenesis, although the offspring are relatively normal in appearance, a number of features in their cortical architecture and function are altered. These include laminar disorganization [14], altered response profiles through neocortical layers [15], specific displacement of GABAergic neurons in the mature neocortex [14,16], and increased levels of GABA A receptors [6,17]. We also observed that interneurons migrating into the neocortex from the ganglionic eminence specifically altered their speed and pattern of movement after MAM treatment [6].…”
Section: Introductionmentioning
confidence: 70%
“…Rat pups treated with MAM on gestational day 15 (GD-15) or GD-17 develop neuropathological and behavioral changes consistent with focal cortical dysplasia ( Paredes et al, 2006 ; Wong, 2009 ; Kim et al, 2017 ) or schizophrenia ( Moore et al, 2006 ; Lodge and Grace, 2009 ; Du et al, 2020 ; Sonnenschein and Grace, 2020 ), respectively. A cortical dysplasia animal model can also be produced by administering MAM to pregnant ferrets (GD-33) resulting in reduced migration of cortical neurons ( Schaefer et al, 2008 ) and increased GABA A receptor expression ( Abbah et al, 2014 ). Studies by Schaefer et al (2008) suggest that the effect of MAM on the migration of cortical neurons in the GD-33 ferret model is due to reductions in reelin , a gene that undergoes epigenetic regulation and encodes a protein with an important role in the migration of cortical neurons in the brains of subjects with various psychiatric disorders (e.g., schizophrenia) ( Ibi et al, 2020 ).…”
Section: Cycad Genotoxins and Neurodevelopmentmentioning
confidence: 99%
“…Alteration in KCC2 expression during development can have dire consequences on cortical formation because it influences the final laminar position of interneurons to reach the neocortex (Fishell & Kriegstein, 2005) and determines the developmental switch of GABAergic neurons from depolarizing to hyperpolarizing (Ben‐Ari, 2014; Ben‐Ari et al, 1989; Kahle et al, 2008; Mueller et al, 1984). There is evidence that common chemicals such as bisphenol A can alter KCC2 expression during brain development and cause neurodevelopmental disorders (Abbah et al, 2014; Abbah & Juliano, 2014; Djankpa et al, 2019). Hence, we hypothesise that MSG can alter KCC2 expression and affect behaviour.…”
Section: Introductionmentioning
confidence: 99%